STEAM-Integrated Problem-Based Learning: Traditional Indonesian Music on Sound Wave Concepts - Cristina Aurelia; Prima Warta Santhalia; Wahyu Hari Kristiyanto (Postgraduate, University of Mataram, 2023)
Conceptual understanding is the level of a student's ability to understand a certain concept and explain it without altering the original meaning. This research aims to determine students' conceptual understanding by using STEAM-integrated Problem-Based Learning on sound wave material.